Enhanced Structural Distortions Allowing for Dicyanophenyl‐substituted Emitters with Outstanding Thermally Activated Delayed Fluorescence Characteristics. (24th August 2017) - Kim, Hyojeong; Yi, Jigyoung; Jo, Bonghyun; Shin, Hee‐Won; Park, Hui Joon; Lee, Suk Joong
Abstract :